Identity and distribution of Bouteloua reederorum (Poaceae: Chloridoideae), a species endemic to Mexico - Sandoval Ortega, Manuel Higinio; Siqueiros Delgado, María Elena; Cerros Tlatilpa, Rosa; Pérez Molphe Balch, Eugenio (Instituto de Ecología, A.C., 2020)
Background and Aims: Bouteloua is one of the most important genera in North American grasslands, especially in Mexico, where 92% of the taxa described for this group are distributed, 25 of which are endemic. One of these is Bouteloua reederorum, which has been confused with B. stolonifera, causing it to be reported in states of the republic where it is not found. The aim of the present work is to clarify the identity of B. reederorum and provide a detailed morphological description with photographs of important structures for its identification, as well as a distribution map for this species.Methods: The material deposited in the herbaria ARIZ, HUAA, HUAP, HUMO, IEB, INEGI, MEXU, XAL, the digital collections MO, P and US, and the platform JSTOR, were reviewed to obtain records of B. reederorum. Based on this information, collection points were determined, which were visited from September 2017 to August 2019 in search of populations of this species, where specimens were collected. The collected material was identified and reviewed to prepare a morphological description accompanied with photographs of important characteristics for the identification of the species. With the obtained records, a distribution map of B. reederorum was made.Key results: Bouteloua reederorum and B. stolonifera can be easily distinguished by several morphological characteristics such as branching of their inflorescences and the ligule shape. Bouteloua reederorum is practically restricted to the Tehuacán-Cuicatlán Valley, located between Puebla and Oaxaca. Although the male spikelets of B. reederorum generally do not have rudimentary florets, they can rarely develop one similar to that of the female spikelets.Conclusions: Bouteloua reederorum is different from Bouteloua stolonifera (= Cyclostachya stolonifera). Phenological studies are necessary to determine if B. reedeorum can be dioecious.